The Evolution of the International Court of Justice’s Approach to the Right of Actio Popularis Before It, Based on Recent Case Law - Zaręba, Szymon (Polish Review of International and European Law, 2026)
The article analyses the jurisprudence of the International Court of Justice (ICJ) relating to the admissibility of actio popularis before it prior to 2020 and then, against this background, demonstrates the extent to which continuity and change can be observed in the Court’s subsequent case law on this topic. The article argues that while the ICJ’s line of jurisprudence on action popularis has generally remained consistent, there has been an important and qualitatively significant evolution in the ICJ’s position over the past few years. This is primarily evident in the Court’s recent acknowledgement of the possibility of bringing actio popularis claims before it based solely on erga omnes norms of customary international law. The text signals some potential challenges this may present. It also highlights that the ICJ still does not seem willing to relax its expectations regarding procedural requirements, such as consent to jurisdiction, which significantly limits the potential impact of allowing actio popularis claims based on norms of customary international law.